2017
DOI: 10.1038/s41598-017-18098-z
|View full text |Cite
|
Sign up to set email alerts
|

Photoreceptor metabolic reprogramming provides survival advantage in acute stress while causing chronic degeneration

Abstract: Photoreceptor death is the root cause of vision loss in many retinal disorders, and there is an unmet need for neuroprotective modalities to improve photoreceptor survival. The biosynthetic requirement of photoreceptors is among the highest in the body, and to meet this demand, photoreceptors maintain their ability to perform aerobic glycolysis. This highly regulated form of glycolysis allows cells to efficiently budget their metabolic needs and may be a critical link between photoreceptor function and surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
148
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(159 citation statements)
references
References 40 publications
11
148
0
Order By: Relevance
“…Photoreceptors are highly sensitive to hypoxia and nutrient deprivation, but the pathway by which they can maintain the metabolite levels to meet their high energy demands is not fully understood (26). Furthermore, studies examining metabolic flux in the retina indicate the need for energy homeostasis across the photoreceptor cell layer and with the RPE to maintain retinal health and visual acuity (27)(28)(29)(30). Therefore, the mitochondria arrangement described in this study may be an important evolutionary development for sharing the level of particular metabolites across the photoreceptor cell layer.…”
Section: Discussionmentioning
confidence: 99%
“…Photoreceptors are highly sensitive to hypoxia and nutrient deprivation, but the pathway by which they can maintain the metabolite levels to meet their high energy demands is not fully understood (26). Furthermore, studies examining metabolic flux in the retina indicate the need for energy homeostasis across the photoreceptor cell layer and with the RPE to maintain retinal health and visual acuity (27)(28)(29)(30). Therefore, the mitochondria arrangement described in this study may be an important evolutionary development for sharing the level of particular metabolites across the photoreceptor cell layer.…”
Section: Discussionmentioning
confidence: 99%
“…2124 PKM2 is expressed by photoreceptors in the retina while PKM1 expression is confined to the inner retina, and ML-265 shows a high degree of selectivity for PKM2 over other isoforms, PKM1, PKR, and PKL. 5,10,12,13,15,17,20–22 Therefore, ML-265 represents an ideal lead molecule to explore the neuroprotective effects of pharmacologically activating PKM2 in photoreceptors. In line with previous reports, ML-265 displayed potent activation of recombinant human PKM2 with a maximum activation of 249 ± 14% (best-fit value ± std.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported that a key regulator of aerobic glycolysis, PKM2, plays a critical function in photoreceptor survival during acute outer retinal stress. 15 PKM2 converts phosphoenolpyruvate (PEP) and adenosine diphosphate (ADP) to pyruvate and ATP in the final rate-limiting step of glycolysis. Photoreceptors maintain expression of PKM2 after differentiation, unlike other neurons, which exclusively express the constitutively active PKM1 isoform following terminal differentation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations